2020
DOI: 10.38021/asbid.833906
|View full text |Cite
|
Sign up to set email alerts
|

Spor Bilimleri Fakültesi Öğrencilerinin Kariyer Değerlerinin İncelenmesi

Abstract: Kasım 2020 tarihinde düzenlenen, 18. Uluslararası Spor Bilimleri Kongresinde sözel bildiri olarak sunulmuştur. ÖzBu çalışmanın amacı üniversite öğrencilerinin kariyer değerlerinin demografik değişkenlere göre nasıl şekillendiğini belirlemektir. Bu amaç doğrultusunda araştırmanın örneklemini Çukurova Üniversitesi Spor Bilimleri Fakültesi bünyesinde bulunan antrenörlük, beden eğitimi öğretmenliği ve spor yöneticiliği bölümünde öğrenim gören 222 öğrenci oluşturmaktadır. Araştırmada veri toplama aracı olarak Schei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Unlike the results of the present study, in their studies they examined the factors affecting career values of associate degree students Şentürk and Buran [24] reported that female participants had higher perceptions between the variable of gender and career values. Eratlı Şirin and Aydın [25] examined the career values of students in the faculty of sports sciences and reported that there were no differences between the variable of gender and sub-dimensions of career values scale. Dinç [14, pp:139] and Öztürk [15, pp.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the results of the present study, in their studies they examined the factors affecting career values of associate degree students Şentürk and Buran [24] reported that female participants had higher perceptions between the variable of gender and career values. Eratlı Şirin and Aydın [25] examined the career values of students in the faculty of sports sciences and reported that there were no differences between the variable of gender and sub-dimensions of career values scale. Dinç [14, pp:139] and Öztürk [15, pp.…”
Section: Discussionmentioning
confidence: 99%